FROM HISTORY TO DECAY: CONDITION SURVEY OF FACADES ON KARET STREET, SURABAYA - Tjia, Darrell Immanuel; Kenny David Ariyanto; Dharmatanna, Stephanus Wirawan (Border: Jurnal Arsitektur, 2025)
Karet street corridor is one of the historical street corridors in Surabaya that picture the blend character of Colonial and Chinese architecture. These unique characteristics started to decrease and even vanish in some buildings in the street, through the development of Surabaya. This research aims to map the existing condition of the facade and outlining possible conservation strategies by using field observation with qualitative analysis. All the sixty two buildings alongside the street corridor will be grouped into four condition levels: excellent, good, fair, and poor that were based on integrity of the facade, the suitability of materials, and the quality of surface finishes. The result showed that in areas with low activity, the damage is more commonly found than one in busy commercial zones. It also revealed that a combination of deterioration pattern and user behaviour affect the conservation strategies that could be applied in these buildings. This study recommends a zoning-based conservation in response to the deterioration of the facade, including full restoration, maintenance for good and fair condition, and preventive action for well preserved buildings. Overall, this research recommends preservation alternatives to maintain the authenticity and cultural significance of Karet street for years to come.